APEXSENSUN: An Open‐Source Package in R for Sensitivity Analysis and Model Performance Evaluation of APEX. (27th September 2018) - Talebizadeh, Mansour; Moriasi, Daniel; Steiner, Jean L.; Gowda, Prasanna; Tadesse, Haile K.; Nelson, Amanda M.; Starks, Patrick
Abstract: The Agricultural Policy/Environmental eXtender (APEX) model is used to evaluate the impact of different land management strategies associated with water availability, soil and water quality, plant growth, and economics. This article presents APEXSENSUN, an open‐source software package that automates global sensitivity analysis and assists with calibration of the APEX model. APEXSENSUN was developed in R programming language and includes regression‐based, derivative‐based, and variance‐based methods, as well as a regional sensitivity analysis method. Evapotranspiration data measured at a research field located at the United States Department of Agriculture‐Agricultural Research Service Conservation and Production Research Laboratory in Bushland, Texas were utilized to illustrate the main features of APEXSENSUN, which are to identify important parameters and assist with calibration. The results from variance‐based methods were in agreement regarding the ranking of top five sensitive parameters including the soil evaporation‐plant factor, root growth‐soil strength, and the coefficient for adjusting the microbial activity function in the top soil layer. The Fourier amplitude sensitivity testing method required the least number of simulations for calculation of the total‐effect sensitivity indices. The Monte Carlo‐based calibration feature of the package was also tested for calculating the posterior parameter distributions and prediction intervals with a desired level of confidence for output predictions. Abstract : Research Impact Statement: APEXSENSUN, an open‐source package that performs global sensitivity analysis and assists with calibration of the APEX model, is described and evaluated.